Why is respiratory protective equipment still an issue in the NHS?. (27th April 2022) - Peters, Christine; Lawton, Tom; Butler, Matt; Waters, Huw; Hughes, Eilir
Abstract : Revised NHS guidance has relaxed infection prevention and control (IPC) requirements for hospitals and GP practices. These authors question why airborne transmission is not more clearly acknowledged and why healthcare workers still do not have access to appropriate personal protective equipment